Модель жизненного цикла знание-емкого бизнес-процесса - Левыкин, В.М.; Чалая, О.В. (Управляющие системы и машины, 2017)
Усовершенствована типовая модель процессного жизненного цикла применительно к знание-емким бизнес-процессам. Модель отличается от существующих проведением адаптации и модернизации бизнес-процесса параллельно с его выполнением на основе новых зависимостей между действиями и используемыми объектами. Удосконалено типову модель процесного життєвого циклу для знання-ємних бізнес-процесів. Модель відрізняється від існуючих проведенням адаптації та модернізацією бізнес-процесу паралельно з його виконанням на основі нових залежностей між діями і використованими об'єктами. The purpose of this article is to develop a model of the lifecycle of the knowledge-intensive business process which would provide an opportunity to improve the process after the completion of the currently executing instance, and while it is running. This will give a possibility to improve the efficiency of process management for the current instance of the process through the use of personal knowledge of workers in the process model. The model of the process lifecycle in relation to the knowledge-intensive business processes is improved. The model includes phases of analysis, re-engineering, deployment and use of the business process. The sequence of the lifecycle phases implements the waterfall strategy. Evolutionary strategy is implemented in the use phase.